Subjects of Analysis. (Karnac Books, 2012)
In this brilliant contribution to psychoanlaytic theory and practice, Ogden has once again challenged psychoanalytic clinicians to expand the conceptual envelope that confines and constricts their work. Sounding the death knell for the positivist view of the patient and analyst as discrete subject and object, he forges a contemporary, decentred entity - the analytic third.